Creativity as the basis of thinking skills development in the process of cognitive learning activity - Inga V. Cherkasova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The paper deals with the creativity as the basis of thinking skills development in the process of cognitive learning activity. Understanding of the creativity and heuristics contents is analysed. The necessity of young generation creative learning development is explained as while studying different subjects and in any human activity creative elements can be come across. As a result, the authors come to the conclusion that the dramatic growth of information volume requires from the person such qualities as being active, initiative, flexible, inventive and also being able to make decisions quickly and correctly. That is impossible without being creative and independent while working.